Visualization of revolving surfaces formation - V A Romanova; G N Oskina; - Giloulbe Mathieu (RUDN Journal of Engineering Research, 2014)
In the paper algorithm software of creation mini-film “Formation of revolving surfaces formation” is considered. This film is essentially a didactic material to the subjects «Computer Graphics» and «Descriptive Geometry».